Attitudes and factors affecting acceptability of self-administered cervicovaginal sampling for human papillomavirus (HPV) genotyping as an alternative to Pap testing among multiethnic Malaysian women. Issue 8 (4th August 2016) - Ma'som, Mahirah; Bhoo-Pathy, Nirmala; Nasir, Nazrila Hairizan; Bellinson, Jerome; Subramaniam, Shridevi; Ma, Yuntong; Yap, Siew-Hwei; Goh, Pik-Pin; Gravitt, Patti; Woo, Yin Ling
Abstract : Objective: The objective of this study was to determine the attitudes and acceptability of self-administered cervicovaginal sampling compared with conventional physician-acquired Papanicolaou (Pap) smear among multiethnic Malaysian women. Method: A cross-sectional study was carried out via interviewer-administered surveys from August 2013 through August 2015 at five government-run, urban health clinics in the state of Selangor. Subjects were participants from an ongoing community-based human papillomavirus (HPV) prevalence study who answered a standard questionnaire before and after self-sampling. The cervicovaginal self-sampling for HPV genotyping was performed using a simple brush ('Just for Me'; Preventive Oncology International, Hong Kong). Detailed data on sociodemographics, previous Pap smear experience, and attitudes towards self-administered cervicovaginal sampling were collected and analysed. Acceptability was inferred using a five-item Likert scale that included six different subjective descriptives: experience, difficulty, convenience, embarrassment, discomfort or pain, and confidence in collecting one's own sample. Results: Of the 839 participants, 47.9% were Malays, followed by 30.8% Indians, 18.8% Chinese and 2.5% from other ethnicities. The median age of the participants was 38 years (IQR 30–48). Some 68.2% of participants indicated a preference for self-sampling over the Pap test, with 95% indicating willingness to follow-up a positive result at the hospital. Age, ethnicity and previous Pap test experience were significant independent factors associated with preference for self-sampling. The older the individual, the less likely they were to prefer self-sampling (adjusted OR 0.94, 95% CI 0.90 to 0.98). The Chinese were less likely to prefer self-sampling (72.6%) than the Malays (85.1%) (adjusted OR 0.57, 95% CI 0.33 to 0.98, p=0.004). Participants who had never undergone a Pap smear were also more likely to prefer self-sampling (88.5%) than women who had undergone a previous Pap (80.9%) (adjusted OR 0.06, 95% CI 0.35 to 0.87). Conclusions: Overall, urban Malaysian women from multiethnic backgrounds found self-sampling to be an acceptable alternative to Pap smear.